1998
DOI: 10.1212/wnl.51.3.890
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and biochemical studies of juvenile parkinsonism linked to chromosome 6q

Abstract: We report the results of pathologic and biochemical studies in a patient with 6q-linked autosomal recessive juvenile parkinsonism (AR-JP). Neuronal loss and gliosis were restricted to the substantia nigra and the locus ceruleus. No Lewy bodies were found, but neurofibrillary tangles and argyrophilic astrocytes were seen in the cerebral cortex and brainstem nuclei. The later findings, which have not been reported previously in AR-JP, suggest the pathologic heterogeneity of 6q-linked AR-JP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
247
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(268 citation statements)
references
References 2 publications
12
247
0
5
Order By: Relevance
“…PD is characterized pathologically by the presence of cytoplasmic proteinaceous inclusions (Lewy bodies), which stain abundantly with ubiquitin (42). Patients with mutations in Parkin do not have Lewy bodies (43)(44)(45). Our observations that Parkin functions in the ubiquitin proteasome degradation pathway coupled with the postmortem observations suggest that Parkin function might contribute to the formation of Lewy bodies and that Lewy body formation may not be required for the development of PD.…”
Section: Discussionmentioning
confidence: 63%
“…PD is characterized pathologically by the presence of cytoplasmic proteinaceous inclusions (Lewy bodies), which stain abundantly with ubiquitin (42). Patients with mutations in Parkin do not have Lewy bodies (43)(44)(45). Our observations that Parkin functions in the ubiquitin proteasome degradation pathway coupled with the postmortem observations suggest that Parkin function might contribute to the formation of Lewy bodies and that Lewy body formation may not be required for the development of PD.…”
Section: Discussionmentioning
confidence: 63%
“…Mutations in the parkin gene are therefore considered to cause loss of ubiquitinprotein ligase activity (Shimura et al 2000). The main histopathological difference between patients with parkin mutations and those with sporadic PD are the absence of Lewy bodies (despite Chen et al 2000) and the restriction of neuronal loss to the substantia nigra and locus caeruleus in patients with parkin mutations (Mori et al 1998). Pathological studies of the brains of patients with AR-JP showed absence of parkin protein (Shimura et al 1999).…”
Section: Parkin (Gene Locus Park2 Omim 602544)mentioning
confidence: 99%
“…Furthermore, many of the monogenic mutations do not lead to development of LBs, a feature that also may be observed in sporadic PD, as well as after administration MPTP. These observations demonstrate that neurodegeneration can occur without the presence of LBs, both in familial and sporadic forms of PD (102,103).…”
Section: Pathological Hallmarksmentioning
confidence: 56%